Sublobar resection for early-stage lung cancer - Sakurai, Hiroyuki; Asamura, Hisao (Translational Lung Cancer Research, 2014)
Since the 1995 report of the prospective randomized trial of lobectomy versus sublobar resection for stage I non-small cell lung cancer (NSCLC) performed by the the Lung Cancer Study Group, lobectomy remains the standard of care for the surgical management of stage I NSCLC. Sublobar resection has been typically used for high-risk patients who are operative candidates but for whom a lobectomy is contraindicated. Recent advances in imaging and staging modalities and improved spatial resolution of computed tomography (CT) scan have refined the presentation and diagnosis of early-stage NSCLC. The detection of small tumors and ground-glass opacity (GGO) appearance associated with a favorable histology have led to the increased use of sublobar resection in many institutes to include good-risk patients. There is an increasing body of evidence that sublobar resection may achieve oncological outcomes similar to those with lobectomy in early-stage NSCLC, especially that 2 cm or less in size. However, whether or not sublobar resection constitutes adequate treatment for small-sized lung cancer or for the radiographic “early” lung cancer such as a GGO-dominant lesion is still being prospectively investigated. Sublobar resection will be expected to play an important role as a primary treatment option for patients with small stage IA NSCLC, based on an anatomical functional advantage over lobectomy as well as comparable prognostic outcomes between sublobar resection and lobectomy.